2016
DOI: 10.1093/bja/aew321
|View full text |Cite
|
Sign up to set email alerts
|

Troponin elevations after non-cardiac, non-vascular surgery are predictive of major adverse cardiac events and mortality: a systematic review and meta-analysis

Abstract: Postoperative myocardial injury is an independent predictor of major adverse cardiac events and mortality within 30 days and 1 yr after non-cardiac, non-vascular surgery. The meta-analysis provides evidence that supports troponin monitoring as a cardiovascular risk stratification tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
66
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 184 publications
(76 citation statements)
references
References 40 publications
(39 reference statements)
7
66
2
1
Order By: Relevance
“…1,[3][4][5]9 The incidence of PMI observed in our study was comparable to that observed, eg, in VISION if using a comparable absolute hs-cTnT-delta criterion. 1,[3][4][5]9 Differences in observed incidence rates found in several previous studies seem to relate to differences in the study populations, definitions of PMI, and the cTn assays used. 1,[3][4][5]9 The VISION study included patients >45 years (mean age, 63 years) irrespective of preexisting coronary artery disease or peripheral artery disease, and therefore at lower cardiovascular risk than in this study (median age, 74 years).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…1,[3][4][5]9 The incidence of PMI observed in our study was comparable to that observed, eg, in VISION if using a comparable absolute hs-cTnT-delta criterion. 1,[3][4][5]9 Differences in observed incidence rates found in several previous studies seem to relate to differences in the study populations, definitions of PMI, and the cTn assays used. 1,[3][4][5]9 The VISION study included patients >45 years (mean age, 63 years) irrespective of preexisting coronary artery disease or peripheral artery disease, and therefore at lower cardiovascular risk than in this study (median age, 74 years).…”
Section: Discussionsupporting
confidence: 87%
“…These findings extend and corroborate previous work on PMI, particularly the VISION study (Vascular Events in Noncardiac Surgery Patients Cohort Evaluation). 1,[3][4][5]9 The incidence of PMI observed in our study was comparable to that observed, eg, in VISION if using a comparable absolute hs-cTnT-delta criterion. 1,[3][4][5]9 Differences in observed incidence rates found in several previous studies seem to relate to differences in the study populations, definitions of PMI, and the cTn assays used.…”
supporting
confidence: 87%
See 3 more Smart Citations